The acceptance of Project-Based Learning (PBL) in classroom practice by Secondary Education teachers - Castellano Almagro, Rafael; Ortiz Colón, Ana Mª; Rodríguez Moreno, Javier (Revista Complutense de Educación, 2025)
Taking into account the didactic challenges that 21st-century society poses for the educational system and for teachers in particular, active methodologies, and more specifically Project-Based Learning (PBL), emerge as a consolidated option in the daily classroom practice of many educational institutions. To this end, the present study aimed to evaluate the classroom practice developed by teachers regarding the Project-Based Learning (PBL) methodology. A total of 279 teachers from seventeen secondary education and high school centers in four autonomous communities in Spain (Andalusia, Extremadura, Murcia, and Valencia) participated in the present research. For this purpose, a Likert-type ad hoc questionnaire, validated by experts, was applied as the instrument. It is a comprehensive instrument divided into three dimensions, focusing on the "Classroom Practice" dimension, composed of 15 items. The main results of this research show that teachers are satisfied with their own classroom practice based on PBL, as it represents the practical framework of a methodology that challenges the erroneous assumptions of education and responds to the new needs of the current educational system.